PENGETAHUAN REMAJA TENTANG HIV/AIDS DAN PERILAKU SEKSUAL BERISIKO (ANALISIS DATA SKRRI TAHUN 2007) - , Desak Made Firsia Sastra Outri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Indonesian Ministry of Health estimates that 75% of AIDS patients in Indonesia are infected with HIV during their adolescence. Lack of information and practical knowledge about how to prevent HIV infection, sexual initiation at an early age, multiple partners and the absence of condom use as well as drug use have contributed to increased risks of HIV/AIDS and other STIs. Objective: To determine the background of adolescentâs knowledge about HIV/AIDS underlying their risky sexual behavior. Method: The study ultilized data from 2007 SKRRI, using cross-sectional study . Participants were adolescents aged 15-24 years. The statistical test used was Chisquare test and ordinal logistic regression with confidence intervals (CI) 95% and p <0.05. Result: Adolescentâs knowledge about HIV/AIDS was quite good. More than 50% of adolescents knew about HIV/AIDS. Adolescents with high knowledge about HIV/AIDS had possibility to have high risky sexual behaviors. At high knowledge about HIV/AIDS infection through sexual intercourse, the adolescents significantly had risky sexual behaviors (OR = 1.36, 95% CI = 1.15 to 1.60). At high knowledge about HIV/AIDS infection without sexual intercourse, the adolescents were found to have lower risky sexual behavior (OR = 0.74, 95% CI = 0.63 to 0.87). Other factors that influenced sexual behavior were gender, age, and education. Conclusion: A high degree of HIV/AIDS knowledge among adolescents does not guarantee the adolescents to have a safe sexual behaviour, that is the use of condom.